IMPACT OF THE PANDEMIC ON THE ORGANIZATIONAL MANAGEMENT OF COMPANIES - María Flores Santacruz, Jessica; Lourdes Martínez Leguizamón, María; Adorno Benítez, Estelvina (Revista Gênero e Interdisciplinaridade, 2023)
In this final degree project called “Impact of the pandemic on the organizational management of companies” whose objective is to analyze the strategies adopted in organizational management by companies during the pandemic, to face the challenges. The qualitative approach was adopted as a study method, using a questionnaire with 10 questions addressed to senior officials of 6 large companies in Ciudad del Este from different fields. The answers were used to analyze the different types of problems that the companies had and mainly to know the strategies that they have used to solve or reduce the effects of these problems. With the research done and the results obtained, it is concluded that the companies were prepared for the crisis, perhaps not for this type of crisis, which is the arrival of the pandemic, but they affirm that they were able to stay in the market thanks to the strategies they used and the skill of its administrators.